2018
DOI: 10.5539/ibr.v11n4p65
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure Determinants in Family Firms: An Empirical Analysis in Context of Crisis

Abstract: The purpose of this paper is to investigate the capital structure of family firms in a context of crisis. Specifically, it aims to discover whether and how the determinants of their capital structure have a different impact on firms' leverage before and during the recent global financial crisis. Considering the pecking order theory (POT), trade-off theory (TOT), and agency theory (AT), this study analyzes 1,502 Italian medium family firms comparing the pre-crisis (2005)(2006)(2007) and crisis (2008)(2009)(2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
3
6
0
Order By: Relevance
“…Here, it was pointed out that big companies tend to be more diversified and have more assets as guarantees to loans, thus, are more ready to access fund sources (Al-Najjar, 2011). The current results showed that asset utilization inversely measures agency conflicts) has a positive and significant effect on the debt, consistent with previous studies (Migliori et al, 2018;Tarus and Ayabei, 2016). Moreover, these findings could be interpreted in line with that risk-efficiency argument which states that an efficient company (common agency problems) has a lower risk of bankruptcy and financial distress, thus, tend to select rise the debt ratio (Migliori et al, 2018).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Here, it was pointed out that big companies tend to be more diversified and have more assets as guarantees to loans, thus, are more ready to access fund sources (Al-Najjar, 2011). The current results showed that asset utilization inversely measures agency conflicts) has a positive and significant effect on the debt, consistent with previous studies (Migliori et al, 2018;Tarus and Ayabei, 2016). Moreover, these findings could be interpreted in line with that risk-efficiency argument which states that an efficient company (common agency problems) has a lower risk of bankruptcy and financial distress, thus, tend to select rise the debt ratio (Migliori et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…In the light of resources independence theory, the family has its network, thus making it easier to access the sources of the funds for the families to increase their debt. The firm's size was found to have a positive effect on the leverage, as gauged by sales, and these findings are in line with Al-najjar (2011), andMigliori, Maturo, andPaolone (2018). This could be the scenario as sales rise, the need for cash also increases particularly, and if the firms are not good at collecting cash, this may resort to using debts to fund their needs.…”
Section: Resultssupporting
confidence: 58%
“…The majority of firms fail as a result of challenges facing managers and owners on financing decisions. This is because, most firms and organizations fail or perform poorly because of diverse challenges managers or owners face regarding financing decisions (Migliori et al, 2018). This phenomenon gained considerable attention among financial economists after the formulation of Modigliani and Miller's (1958) capital structure irrelevance theory.…”
Section: Capital Structurementioning
confidence: 99%
“…Many researchers such as Migliori et al (2018) and Salam and Shourkashti (2019) maintain that there is an optimal capital structure, which involves the one that increases the wealth and value of shareholders whilst minimizing the cost of capital. However, Pinto and Quadras (2016) argue that it is difficult for managers of firms to decide an accurate and optimal capital structure, since it involves uncertainty and risks.…”
Section: Capital Structurementioning
confidence: 99%
See 1 more Smart Citation